2007
DOI: 10.1111/j.1472-765x.2007.02268.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of lethal and sublethal injury in food-borne bacterial pathogens exposed to high-intensity pulsed-plasma gas discharges

Abstract: Aims:  To apply scanning electron microscopy, image analysis and a fluorescent viability stain to assess lethal and sublethal injury in food‐borne bacteria exposed to pulsed‐plasma gas discharges (PPGD). Methods and Results:  The fluorescent redox probe 5‐cyano‐2,3‐ditolyl tetrazolium chloride (CTC) was used for enumerating actively respiring cells of Campylobacter jejuni, Escherichia coli, Listeria monocytogenes, Staphylococcus aureus and Salmonella enterica serovar Typhimurium that were suspended in sterile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Yeasts and bacteria spores show D-values of up to 6 min because of the polysaccharides around the cell walls, whereas viruses are even more resistant [166]. It has been shown by Rowan et al [183] that, as for heat treatment, a significant number of cells are resistant. The resistant cells show significant respiratory activity but do not exhibit growth and therefore can be classified as viable but non-culturable.…”
Section: Basic Mechanisms Of Microbial Inactivation and Cleaningmentioning
confidence: 96%
“…Yeasts and bacteria spores show D-values of up to 6 min because of the polysaccharides around the cell walls, whereas viruses are even more resistant [166]. It has been shown by Rowan et al [183] that, as for heat treatment, a significant number of cells are resistant. The resistant cells show significant respiratory activity but do not exhibit growth and therefore can be classified as viable but non-culturable.…”
Section: Basic Mechanisms Of Microbial Inactivation and Cleaningmentioning
confidence: 96%
“…Rowan, et al [48], applied scanning electron microscopy, image analysis, and a fluorescent viability stain to assess lethal and sublethal injury in food-borne bacteria exposed to Pulsed-Plasma Gas Discharges (PPGD). The fluorescent probe was used for enumerating actively respiring cells of Campylobacter jejuni, Escherichia coli, Listeria monocytogenes, Staphylococcus aureus and Salmonella thyphimurium [48]. These authors reported a good agreement between the use of the respiratory staining and direct colony counting for enumerating untreated bacteria.…”
Section: Concerns About Viabilitymentioning
confidence: 99%
“…After a physical preservation treatment a population of bacteria contains three physiologically different types of cells: uninjured cells that are capable of growth and multiplication equally well in selective and nonselective culture media; injured cells that are capable of multiplication in a nonselective medium but not in a selective medium; and dead cells, which are incapable of multiplication under any conditions (Wuytack et al 2003). Injury of microorganisms can be induced by pulsed-plasma gas discharges (Rowan et al 2008), sublethal heat, freezing, freeze-drying, drying, irradiation, high hydrostatic pressure, aerosolization, dyes, sodium azide, salts, heavy metals, antibiotics, essential oils, sanitizing compounds, and other chemicals or natural antimicrobial compounds (Wesche et al 2009). These mild preservation methods can cause denaturation of cellular proteins, enzymes, or nucleic acids, and they can lead to oxidative stress or physical damage of cell membrane proteins and lipids, and bacterial cell lysis (Alvarez-Ordonez et al 2009;Kobayashi et al 2005;Dlamini and Buys 2009).…”
Section: Introductionmentioning
confidence: 99%